ENHANCING SELF-EFFICACY AND ASSERTIVENESS AMONG STUDENTS EXPERIENCING ACADEMIC ANXIETY THROUGH COGNITIVE RESTRUCTURING-BASED GROUP COUNSELING - Hananto, Ipung; Utami, Ferisa Prasetyaning; Rosyidah, Hani’; Setiawati, Rini (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Self-efficacy is a crucial factor in supporting individuals’ success during the learning process. Students who believe in their own potential tend to achieve optimal performance. Assertiveness is also an important factor in developing effective interpersonal relationships. In the pursuit of academic and non-academic achievement, students are often confronted with challenges such as anxiety. This study aims to examine the effectiveness of group counseling using cognitive restructuring in enhancing self-efficacy and assertiveness among students of SMPN 11 Kota Magelang who experience academic anxiety. This study employed a quasi-experimental method with a pretest-posttest design and involved 18 students selected through purposive sampling. The results of data analysis demonstrated an increase in both variables. Therefore, it can be concluded that cognitive restructuring-based group counseling is effective in enhancing students’ self-efficacy and assertiveness.